(untitled) (Research, Society and Development, 2021)
The objective of this work was to compare two oily effluent treatment systems, batch process and membrane separation process (PSM). In the batch process an organophilic clay was used and in the PSM a low cost ceramic membrane was used. A bofe clay was used as raw material for the preparation of organophilic clay prepared with surfactant, via direct method and characterized by X-ray diffraction. The sorption properties of this organoclay were evaluated to remove oil. The low-cost, disc-shaped ceramic membrane was obtained from natural bofe clay from Boa-Vista, Paraíba, Brazil. The uniaxial dry compaction method and sintering at 650 °C was used. The membrane was characterized by XRD and water permeability and its performance was evaluated by oil/water emulsion separation tests from a synthetic effluent, using a stainless steel module under the conditions of initial concentration of the emulsion 125 mg.L-1, temperature of 25 °C and pressure of 2.0 bar. It is concluded that the two processes (PSM and batch system using bofe organophilic clay as adsorbent) can be used and are promising for the treatment of oily water.